(untitled) (Journal of Economic Research & Business Administration, 2016)
Nowadays it is almost impossible to ensure the competitiveness of producers in the domestic and foreign markets without investments. The processes of qualitative and structural changes in world commodity producers and market infrastructures are taking place via investments. Investing determines the economic growth, the social situation in the region, providing jobs, and also it determines country’s economy. Today, attracting investments by issuing financial instruments are getting more popular. This is facilitated by a favorable investment climate in the country. In any country the investing level is directly related to the level of investment climate and its determinants. The article discusses the importance of foreign investment in Kazakhstan, as well as analyzes the ways of their attraction. Considering the features, it is possible to identify barriers of capital inflow in Kazakhstan and main ways of investment policy.